Project development of recommendation system for improving the energy efficiency of residential buildings - Дубинский, Алексей Георгиевич (Technology audit and production reserves, 2015)
This work is devoted to the project of creating the decision support system for improving the energy efficiency of buildings. The main objective is to determinate the structure of this information system and set the plan for further work. The main parts of the system are: 1) an expert system with knowledge base of improving energy efficiency methods, 2) subsystem for modeling heat balance, 3) decision support subsystem for alternatives comparison, 4) database of current market prices. There are several required external data sources: users – information about the building, economic criteria and limitations; experts – knowledge for expert subsystems; distributors – market prices; and automatically entered data about environment state. For heat balance modeling, we will use the open source software solution like OpenBEM. The expert system will be based on the set of production rules. External visual editor is required for describing the plan of building in 2D-layout. The data processing will be based on the web 2.0 approach, so users can add and evaluate information. Software implementation of business logic and database layers will be designed for deployment in the cloud. The user interface is the web-client with html5 technology. The next step for this project development is designing the expert system. After that, we plan to determine the "minimum valuable product» (by the "Lean Startup" approach) and start the iterative development process in the agile framework, like Scrum.